User Tools


$$ R = \frac{ \displaystyle{\sum_{i=1}^n (x_i-\bar{x})(y_i- \bar{y})}}{\displaystyle{\left[ \sum_{i=1}^n(x_i-\bar{x})^2 \sum_{i=1}^n(y_i-\bar{y})^2\right]^{1/2}}} $$

$$ R = \frac{ \displaystyle{\sum_{i=1}^n (x_i-\bar{x})(y_i- \bar{y})}}{\displaystyle{\left[ \sum_{i=1}^n(x_i-\bar{x})^2 \sum_{i=1}^n(y_i-\bar{y})^2\right]^{3/7}}} $$

\begin{align*} e^x & = 1 + x + \frac{x^2}{2} + \frac{x^3}{6} + \cdots \\ & = \sum_{n\geq 0} \frac{x^n}{n!} \end{align*}


CL Wiki

Institute of Computational Linguistics – University of Zurich